2022
DOI: 10.1017/s1047951121005199
|View full text |Cite|
|
Sign up to set email alerts
|

The role and efficacy of routine high-sensitivity troponin T screening in paediatric COVID-19

Abstract: Objective: We aimed to evaluate the efficacy and role of high-sensitivity troponin T in children with a confirmed SARS-CoV-2 infection and also the correlation of troponin T levels with symptoms, and echocardiographic findings were analysed. Methods: Two hundred and fourteen patients with a confirmed SARS-CoV-2 infection between the dates of 28 March and 15 August 12020 were enrolled in this retrospective single-centre study. Patients with comorbidities and diagnosed as multisystem infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In contrast to this report, only one patient with elevated troponin had an underlying disease and required mechanical ventilation. Ramoglu et al [ 10 ] evaluated 214 pediatric patients, and troponin T levels were elevated in 15 (7%) patients. Troponin T positivity was significantly higher in patients under 12 months, and CRP levels were elevated in 46.7% of patients with troponin positivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to this report, only one patient with elevated troponin had an underlying disease and required mechanical ventilation. Ramoglu et al [ 10 ] evaluated 214 pediatric patients, and troponin T levels were elevated in 15 (7%) patients. Troponin T positivity was significantly higher in patients under 12 months, and CRP levels were elevated in 46.7% of patients with troponin positivity.…”
Section: Discussionmentioning
confidence: 99%
“…However, COVID-19 rarely can cause cardiac disorders in children during acute infection or the resulting multisystem inflammatory syndrome in children (MIS-C) [ 7 ]. There are limited studies in the literature on the use of troponin levels and the potential role in predicting the cardiac involvement of COVID-19 in children [ 8 10 ]. In addition, when to have a consultation for a cardiology specialist is not clear, and the previous studies reported an increased workload of the pediatric cardiology department [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…29 Additionally, children with acute SARS-CoV-2 infection may also present with elevated troponin T levels. 30,31 Lymphopenia has been recognized as a potential marker for assessing the severity of COVID-19 in adults, though it is less common in children. [32][33][34] Moreover, lymphopenia has been observed to be a differentiating factor from children with Kawasaki disease.…”
Section: Discussionmentioning
confidence: 99%